CONSTITUTIONALITY AND ANTARA AS AN OPTIMIZATION OF GOVERNMENT INVESTMENT IN THE INDONESIAN CONSTITUTIONAL SYSTEM - Siti Yunita Sari; Faisal Faisal (Inspiring Law Journal, 2026)
The establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara) represents a government initiative to optimize the management of state assets through a sovereign wealth fund (SWF) scheme derived from the consolidation of several strategic state-owned enterprises. This institution is expected to function as a driving force for national economic growth, provide alternative sources of development financing, and reduce the country’s dependence on foreign loans. However, the process of establishing Danantara has generated debate due to the relatively short legislative process, limited public participation, and remaining concerns regarding transparency and accountability in its management. This study aims to examine the position of Danantara in supporting national economic development, analyze the oversight mechanisms for managing the state’s strategic assets, and assess its conformity with constitutional principles as stipulated in Article 23 and Article 33 of the 1945 Constitution of the Republic of Indonesia. The research employs a normative juridical legal research method using statutory, conceptual, historical, analytical, and case approaches. Research data were obtained through library research consisting of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively to produce systematic and comprehensive legal arguments. The findings indicate that Danantara plays a significant role in supporting national development. Nevertheless, several weaknesses remain, particularly in terms of transparency, oversight mechanisms, and the potential concentration of authority that may not fully align with the principle of checks and balances. This situation reflects a gap between constitutional values and the practical implementation of Danantara’s establishment. Therefore, strengthening regulations, improving transparency, and encouraging public participation are necessary to ensure that Danantara operates in accordance with constitutional principles, is grounded in economic democracy, and truly serves the greatest prosperity of the people.